Does diversity improve profits and shareholder returns? Evidence from top rated companies for diversity by DiversityInc. (June 2017) - Filbeck, Greg; Foster, Benjamin; Preece, Dianna; Zhao, Xin
Abstract: In this study, we examine the relationship between the diversity efforts of firms listed in DiversityInc's list of Top 50 Companies for Diversity and their financial performance. We examine both an announcement effect and the risk-adjusted performance of diverse firms to a matched sample and the S&P 500 index. We find a positive effect related to the announcement of the DiversityInc Top Companies for Diversity list. When examining long-term performance using the risk-adjusted performance of listed companies, DiversityInc firms outperform the S&P 500 index but have performance that is either indistinguishable or inferior to a matched sample. DiversityInc firms exhibit superior return on assets compared to the matched sample, but this difference is explained by differences in firm size. Overall, we find limited support that inclusion in DiversityInc's list of top firms for diversity indicates improved performance over a matched sample.